Numerical Alpha Archive Training System in Accordance with the Archival Code for High School Teachers in Medan City - Juliaty, Tetty; marhaini; Situmorang, Syafrizal Helmi; Sembiring, Beby Karina Fawzeea; Pandia, Komariah (Talenta Publisher, 2019)
Poor management of archives has the potential to cause loss and damage to records or documents. And cause difficulty finding back important archives such as securities. Not a few administrative staff and officials need a lot of time to find back the archived files. Poor archival storage and management are common in companies, including schools. Mulia Medan Private Vocational School, one of which is still not doing the archiving system correctly, where the storage system is not in accordance with the archival rules. Unfortunately, it is difficult for teachers to get the latest archival training, even since 13 years ago when schools were owned by regional autonomy, the gap between regional teachers' competencies and those at the center was farther. Regions are difficult to get the latest competency training in their fields. Then the lack of local government budget funds, schools and also related individuals becomes even more complex problems. Therefore the need for the latest archival training according to the rules has been very urgent especially for vocational teachers in the city of Medan, to prepare graduates who are ready to work. Administrative staff also need to gain competency in the archiving of alphanumeric systems in accordance with the rules of archiving and standards. For this purpose, teachers and administrative staff need to be given training and mentoring, and the results can be seen as a significant improvement in the ability and skills in organizing records after participating in training. The alphanumeric archive storage system is very helpful for schools in arranging archives according to RI rules. For this reason, adequate facilities and infrastructure are needed in schools, so that the support of school principals in the application of proper and proper records management is urgently needed so that teachers and administrative staff can realize them immediately at school.